Introduction to carbon dioxide sequestration–based cementitious construction materials - Pacheco-Torgal, F. (2018)
This chapter briefly reviews important issues that justify the importance of carbon dioxide sequestration. It includes carbon dioxide emissions and projections, global warming consequences namely extreme weather events, ocean acidification, sea level rise, economic losses, the increase of vector-borne illnesses, or even the revival of long dormant deadly bacteria and viruses. Comments about the Conference of parties are made with a special attention for the China situation. Comments are also made about the shortcomings of market-based instruments to try to reduce carbon dioxide emissions. A book outline is also included.